Two novel HLA‐C alleles, HLA‐C*02:02:34 and HLA‐C*03:369, were identified in the same individual. (16th April 2018) - Valatkaite‐Rakstiene, B.; Cekauskiene, R.; Griskevicius, L.; Jakubauskas, A.
Summary: Two new HLA class I alleles, HLA‐C*02:02:34 and HLA‐C*03:369, were characterized in a single Polish bone marrow donor.